Body Mass Index and Western Ontario & McMaster Universities Osteoarthritis Index in Patients with Knee Osteoarthritis in Dr. Hasan Sadikin General Hospital, Bandung in November 2012 - Mohamad Dat, Ainna Binti; Prabowo, Tertianto; Tahid, Alwin (Althea Medical Journal, 2015)
Background: Osteoarthritis is one of the major disabilities among elderly. One of its well-recognized potent risk factors is obesity. The aim of this study was to identify the body mass index and severity of knee osteoarthritis patients who were treated in Dr. Hasan Sadikin General Hospital Bandung.Methods: A descriptive study was carried out to 9 patients of the Medical Rehabilitation Policlinic at Dr. Hasan Sadikin General Hospital Bandung in November 2012. Patients were diagnosed as having knee Osteoarthritis based on American College of Rheumatology clinical classification. Exclusion criteria were patient having previous trauma in spine and lower limb, having bleeding disorder like hemophilia, incomplete data in medical records and incomplete data in questionnaire. Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) was used to measure the intensity of pain, stiffness, and functional difficulty.  The weight (kg) and height (cm) of the patients were measured and the Body Mass Index was calculated by Weight (kg)/Height² (m). The data were analyzed using frequency distribution.Results: The patients who came to the Medical Rehabilitation Policlinic had ranged in age from 57 to78 years, mostly female with knee Osteoarthritis bilateral. Out of 9 patients, 5 patients were overweight, followed by normal BMI and obese type I. Patient with obese type 1 had the highest WOMAC score.  Conclusions: Most of the patients with knee osteoarthritis bilateral are overweight and the patient with obese type 1 has the highest WOMAC score. DOI: 10.15850/amj.v2n3.521